Clinical Characteristics of Juvenile Myasthenia Gravis in Southern China - Huang, Xin; Li, Yingkai; Feng, Huiyu; Chen, Pei; Liu, Weibin (Frontiers in Neurology, 2018)
Objectives To describe the clinical profile, clinical outcomes and factors that may affect the outcome of juvenile myasthenia gravis (JMG) patients in southern China. Methods We reviewed information relating to JMG patients treated and evaluated at the First Affiliated Hospital, Sun Yat-sen University, between 1998 and 2015. The study involved 327 JMG patients who had been followed up for ≥1 year. Results Overall, 77.4% patients showed initial symptoms in the prepubertal period (<12 years). 306 patients showed only ocular symptoms at onset. By the final follow-up, 61 ocular myasthenia gravis (OMG) patients (61/306, 19.9%) had developed generalized myasthenia gravis (GMG). Anti-acetylcholine receptor antibodies (AChR-Ab) titer was an independent risk factor for generalization. Eleven patients (3.4%) experienced spontaneous remission, but four relapsed. Low-dose oral prednisone (0.25 mg/kg) was administered when symptoms did not significantly improve after pyridostigmine treatment. Immunosuppressants were administered when prednisone was unsatisfactory. Optimal outcome was achieved in 59.6% of patients. Specifically, 60 patients (18.3%) attained complete stable remission (CSR), 12 (3.7%) attained pharmaceutical remission (PR), and 123 (37.6%) attained minimal manifestation (MM). In total, 53 OMG patients (21.5%) attained CSR, a significantly higher proportion than among the GMG patients (8.6%, P = 0.009). Moreover, 67.2% of patients with duration <2 years showed significant clinical improvement compared with 46.3% of those with duration >2 years (P < 0.001). Thymectomy did not exhibit definite efficacy for JMG patients. Conclusion There was a low frequency of cases positive for AChR-Ab in the Chinese population. AChR-Ab titer was revealed as an independent risk factor for generalization. Low doses of prednisone could treat JMG effectively with few side effects.